Presence of Microplastics in Windowpane Oyster Placuna placenta and the waters from the Tambak Lorok Coastal Area in Central Java, Indonesia - Eduard Meirenno Tielman; Lisa F. Indriana; Ita Widowati; Ambariyanto Ambariyanto (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Indonesia is the second-largest contributor of plastic debris in the world. The abundance of plastic debris and the bioavailability of its fragmented form known as Microplastics (MPs; < 5 mm of size) can be dangerous for marine environments. This study investigates the presence of MPs in the sea water and marine organisms (Placuna placenta) at Tambak Lorok Waters located at the coast of Semarang city, Central Java, Indonesia. All of the microplastics collected from both samples were identified by their shape, color, size (using Olympus Stereo Microscope), and polymer type (using Fourier Transform Infra-Red Spectroscopy/FTIR). The study found that the Microplastic concentration in the water samples had an average of 12.6 particles.L-1, where the color and size distribution were predominantly blue colored fragments sized less than 50 µm. Examination of the study area showed that microplastics concentration in P. placenta was 1 item and 0.033 items.g-1 for each of the organism. Whereas for physical aspects of microplastics found in the oysters showed the blue colored fibers with range size 300-1000 µm were mostly present. Majority of the polymer types of microplastics found in this study were low-density polyethylene, nylon, polystyrene, and polypropylene. Data from this study shows that microplastics were present in the Tambak Lorok coastal waters. However, there was no significant statistical correlation between the concentration of microplastics in the seawater and the P. placenta, the presence of microplastics in the seawater were found to be ingested by the P. placenta.